Performance of Shariah Contracts in Islamic Banking: A Bibliometric Analysis - Mohamad Khalid Yunus bin Mansor; Muhammad Luthfi bin Mohammad Masruh (Cyber Media Indonesia, 2026)
This study aims to systematically review and visualise the intellectual structure and research landscape concerning the performance of Shariah contracts in Islamic banking, addressing existing gaps in comprehensive bibliometric mapping across major contract types. It seeks to identify key themes, influential contributors, and citation patterns to provide a framework for future empirical and theoretical research. The research employed a quantitative bibliometric analysis using data sourced from Scopus and Web of Science (WoS) databases. A total of 499 publications spanning from 1996 to 2025 were analysed after a rigorous deduplication process using ScientoPy. The study utilised VOSviewer and ScientoPy software tools to visualise publication growth, keyword co-occurrences, and collaborative networks. The findings reveal a significant and sustained increase in research output, particularly peaking between 2024 and 2025. Malaysia emerges as the leading contributor, with the International Islamic University Malaysia (IIUM) ranking as the top institution. Thematic analysis indicates a shift from general comparative studies to specific instruments like Sukuk and Musharakah, with emerging trends focusing on financial stability, Islamic Social Finance, and the integration of Fintech, such as Blockchain.